Calibration of normalised CES production functions in dynamic models - Rainer Klump; Marianne Saam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Normalising CES production functions in the calibration of basic dynamic models allows to choose technology parameters in an economically plausible way. When variations in the elasticity of substitution are considered, normalisation is necessary in order to exclude arbitrary effects. As an illustration, the effect of the elasticity of substitution on the speed of convergence in the Ramsey model is computed with different normalisations.
Keywords: E27; E24; O41; 330; CES production functions; normalisation; calibration; Ramsey model